ECTOPIC WARTHIN’S TUMOUR MASQUERADING AS INFECTED BRANCHIAL CYST - Sheikh, Nadeem Ahmed; Gilani, Syeda Saadia; Raja, Nouman ul Haq; Nadeem, Kanwal (Journal of Ayub Medical College Abbottabad, 2019)
Salivary gland tumours are relatively uncommon but they present globally regardless of age. Most of these tumours are benign and involve the parotid gland. Though strictly confined to the parotid gland, Warthin’s tumours can exceptionally present at an ectopic site of head and neck. Of particular significance is its striking similarity with a lymph node, an inclusion cyst, branchial cyst or a malignant mass, especially when it presents in the upper cervical region. Keywords: Salivary gland; branchioma; head and neck neoplasms, Warthin’s Tumour